Modulation of sperm motility using cell-penetrating peptides - Santiago, Joana Filipa Marques (2017)
The large number of unintended pregnancies worldwide due to the non-use or failure of contraceptive methods and the fact that male contraceptives are limited to condom and vasectomy, highlight the urgent need for the development of new contraceptive methods. The mechanism of sperm motility acquisition in the epididymis constitutes an ideal target for new pharmacological male contraceptives since only the post-testicular sperm maturation is affected. It is known that protein phosphatase 1 subunit gamma 2 (PPP1CC2), a PPP1 isoform only present in testes and sperm, is essential for sperm motility acquisition. Protein-protein interactions (PPIs) have emerged as a promising class of drug targets and cell-penetrating peptides (CPPs) represents a recognized intracellular delivery system to target PPIs. The main goal of this work is to modulate PPP1CC2 complexes and, consequently, spermatozoa motility using peptides covalently coupled to CPPs. The results showed that both peptides tested could modulate sperm motility with a short incubation period, generally increasing the number of immotile spermatozoa. Additionally, we demonstrated that the peptide sequence that mimics the interaction interface between PPP1CC2 and a sperm-specific interactor – Akinase anchor protein 4 (AKAP4) – disrupted the PPP1CC2-AKAP4 interaction, resulting in arrest of sperm motility. The peptide that mimics the 22 amino-acid C-terminus of PPP1CC2 possible acts by disrupting the interaction between PPP1CC2 and isoform-specific interactors. Fifty putative isoform-specific interactors of PPP1CC2 C-terminus were identified by mass spectrometry and one of them was further validated (GPx4), suggesting new targets for similar contraceptive agents. In conclusion, this work confirmed the potential of CPPs to deliver peptide sequences that target unique PPIs in spermatozoa, clarified the mechanism of action of the peptides testes and identified other potential targets for new male contraceptives.